Controls on coastal saline groundwater across North America - Daniel V Kretschmer; Holly A Michael; Nils Moosdorf; Gualbert H P Oude Essink; Marc F P Bierkens; Thorsten Wagener; Robert Reinecke (Environmental Research Letters)
Groundwater is crucial to sustaining coastal freshwater needs. About 32 million people in the coastal USA rely on groundwater as their primary water source. With rapidly growing coastal communities and increasing demands for fresh groundwater, understanding controls of continental-scale coastal groundwater salinity is critical. To investigate what hydrogeological factors (e.g. topography, hydraulic conductivity) control coastal saline groundwater at continental scales, we have simulated variable-density groundwater flow across North America with the newly developed Global Gradient-based Groundwater Model with variable Densities (G ^3 M-D). The simulation results suggest that under a steady climate and pre-development conditions (i.e. steady 30-year mean groundwater recharge, no withdrawals nor sea level rise) saline groundwater is present in 18.6% of North America’s coastal zone, defined as up to 100 km inland and up to 100 m above mean sea level. We find that the coastal zone is particularly vulnerable to containing saline groundwater at low hydraulic gradients (<10 ^−4 ) and large hydraulic conductivities (>10 ^−2 m d ^−1 ). To analyze model parameter sensitivities, i.e. which parameters control the resulting distribution of saline groundwater, we utilize the inherent spatial model variability. We find that hydraulic gradient, topographic gradient, hydraulic conductivity, and aquifer depth are important controls in different places. However, no factor controls coastal groundwater salinization alone, suggesting that parameter interactions are important. Using G ^3 M-D based on G ^3 M, a model that previous work found to be strongly controlled by topography, we find no controlling influence of recharge variability on the saline groundwater distribution in North America. Despite a likely overestimation of saline interface movement, the model required 492 000 years to reach a near-steady state, indicating that the saline groundwater distribution in North America has likely been evolving since before the end of the last ice age, approximately 20 000 years ago.